Performance Assessment of a Fully Automated Deep Sequencing Platform for HCV Resistance Testing. Issue 6 (August 2019) - Rodriguez, Christophe; Mercier-Darty, Mélanie; Soulier, Alexandre; Poiteau, Lila; Wlassow, Mélanie; Fourati, Slim; Hézode, Christophe; Pawlotsky, Jean-Michel; Chevaliez, Stéphane
Background: International liver society guidelines recommended to perform HCV resistance testing at baseline of first-line therapy with certain combination regimens or prior to retreatment in patients previously exposed to a direct-acting antiviral (DAA) containing regimen. Currently, no standardized assays have been developed as purchasable kits for HCV resistance testing. The aim of this study was to evaluate the performance of the Sentosa SQ HCV Genotyping Assay, a novel deep sequencing-based assay, to identify resistance-associated substitutions (RASs) in the NS3 protease, NS5A protein domain I and NS5B polymerase regions for patients infected with HCV genotypes-1a and 1b. Methods: Serum samples collected from patients with chronic hepatitis C infection who failed to achieve a sustained virological response after receiving a DAA-containing treatment regimen were extracted and sequenced by two methods including population sequencing of the NS3, NS5A and NS5B coding region reference method and the deep sequencing-based Sentosa SQ HCV Genotyping Assay. Results: A high concordance rate with Sanger sequencing, the reference method, was found for the NS3, NS5A and NS5 coding regions, regardless of the genotype-1 subtypes. The deep sequencing-based assay was more sensitive than population sequencing to detect minority variants, representing less than 10% of the viral populations, but also some variants representing up to 30% of the viral quasispecies, as expected. Conclusions: The Sentosa SQ HCV Genotyping Assay can be confidently used in clinical practice in the indications of HCV resistance testing for these subtypes. Technical improvements are now required to allow for pangenotypic coverage.